ANALISIS PENGGUNAAN SAKARIN DAN SIKLAMAT PADA MANISAN BUAH YANG DIJAJAKAN DI PASAR RAME MEDAN - Jeanny Zulyana; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Fruit candied is a kind of food which many people like to consume. In the production, producers often use artificial sweetener to replace with saccharin and cyclamate which compare to its sweetness and the cost give more benefit. However, refer to a research, if consuming these saccharin and cyclamate can cause migrain and for long term can cause cancer. The purpose of this research was to know the using of cyclamate and saccharin in the fruit candied and whether the content are fulfiilled the standard of quality. This was a descripitve observational research. The location was in Pasar Rame Medan. The data was gained from the analysis of cyclamate and saccharin by qualitative, with color test extraction and precipitation method, and by quantitative with spektrophotometri Nova and acid alkali titration method. Both were analyzed in Biochemical and Chemical of Food Laboratory, FMIPA USU. The results were compared with preservative sweetener according to SNI 01-6993-2004 about food addictive in artificial sweetener, qualified using based on food category . From the results of the research to 7 samples that being tested, fruit candied were contained cyclamate and saccharin as the artificial sweetener. The content of the artificial sweetener that being used also exceed the permitted level according to SNI 01-6993-2004 that is 500 mg/kg. Therefore, fruit candied which is sold at Pasar Rame Medan is not safe to be consumed. According to the fact, people have to be more aware in buying the fruit candied at Pasar Rame Medan. Beside that, the manufacturer also need to be warned not to use the artificial sweetener such as cyclamate and saccharin, that exceed the permitted level of usage because can harm the health of consumers and also break the law. Key Word  :  Artificial Sweetener, Saccharin, Cyclamate, Fruit Candied